Parents' perception of quality of life and impact on the family of dental fluorosis treatment: Case report - Valdiviezo Dioses, Geraldine Alexia (2024)
Objective: To report the parents' perception of the quality of life and impact on the family of dental fluorosis treatment. Case report: A 10-year and 6-month-old male patient attended the Dental Clinic of Universidad Clínica del Sur (Lima, Peru) accompanied by his mother, who requested treatment due to the “white spots” that she observed on her son's teeth. The intraoral clinical examination revealed demarcated and diffuse opaque lesions compatible with dental fluorosis. For diagnosis, the Thylstrup and Fejerskov Index was used, and to evaluate the oral-health-quality of life, the Peruvian version of the Parental-Caregiver Perceptions Questionnaire (P-CPQ) and the Family Impact Scale (FIS) were used. The dental treatment included prophylaxis, oral hygiene informations, and sealants. Dental fluorosis was treated by microabrasion, remineralization and dental restorations. Conclusion: Microabrasion, remineralization, and restorations performed to treat dental fluorosis positively impacted the OHRQoL of a 10-year-old male patient and his family according to the mother's perception.